Performance enhancement of solar still through efficient heat exchange mechanism – A review. (5th March 2017) - Kabeel, A.E.; Arunkumar, T.; Denkenberger, D.C.; Sathyamurthy, Ravishankar
Highlights: The paper analyzes the effect of various heat exchange mechanisms to augment still productivity. It is possible to augment the output of solar distillation systems with internal energy storage. The effective heat extraction from the tubular solar still significantly increased the productivity. Abstract: The available water sources are insufficient to meet long-term requirements. People can survive for days, weeks, or months without food, but cannot live for more than a week without water. The requirements of water for domestic and industrial use have also increased substantially over the years. Also the limited supply of fresh water in many parts of the world has also resulted in purification of sea water, waste water and brackish water for fresh water production. So fresh water production has rightly been accorded a high priority in many countries' development. This review article analyzes the effect of various heat exchange mechanisms adopted by researchers to augment the water production from different solar still designs. Many authors have designed and tested conventional solar stills, modifications in the basin geometry and integration with collectors. It is also possible to augment the output of solar distillation systems with internal energy storage. The energy storage of the basin can be further increased by phase change materials (PCM), thermal energy storage materials (TESM) and inducing a larger temperature difference between the water in the basin and the glass. The present paper describes a comprehensive review on modifications done on solar stills to improve the productivity. Also the percentage improvement in the productivity of the modifications stills are shown in these articles.